2016
DOI: 10.1007/s40641-016-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Lessons on Climate Sensitivity From Past Climate Changes

Abstract: Over the last decade, our understanding of climate sensitivity has improved considerably. The climate system shows variability on many timescales, is subject to non-stationary forcing and it is most likely out of equilibrium with the changes in the radiative forcing. Slow and fast feedbacks complicate the interpretation of geological records as feedback strengths vary over time. In the geological past, the forcing timescales were different than at present, suggesting that the response may have behaved differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 106 publications
1
44
0
Order By: Relevance
“…Nevertheless, this paleodata‐based analysis suggests that the equilibrium climate sensitivity for present‐day is more at the high end with respect to reported values in the IPCC AR5 report (e.g., Thematic Focus Element 6 in Stocker et al, ). Other paleostudies applying climate models of different complexity to various different climate background states, which have been up to 16 K warmer than the preindustrial climate, also found a state dependency in S[CO2,LI] with mean numbers ranging from 0.6 to 1.6 K W −1 m 2 (von der Heydt et al, ).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 95%
“…Nevertheless, this paleodata‐based analysis suggests that the equilibrium climate sensitivity for present‐day is more at the high end with respect to reported values in the IPCC AR5 report (e.g., Thematic Focus Element 6 in Stocker et al, ). Other paleostudies applying climate models of different complexity to various different climate background states, which have been up to 16 K warmer than the preindustrial climate, also found a state dependency in S[CO2,LI] with mean numbers ranging from 0.6 to 1.6 K W −1 m 2 (von der Heydt et al, ).…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 95%
“…Analyses of paleoreconstructions (Köhler et al, 2015; K2015 in the following) and paleoclimate simulations (Friedrich et al, 2016; F2016 in the following), covering the late Pleistocene, have suggested that climate sensitivity might not be a constant parameter of the climate system but a state-dependent variable that increases toward warmer climates. Most other studies on this topic indicate a similar behavior, including a review that covers a wide range of colder and warmer climate states (von der Heydt et al, 2016). However, there have also been studies using general circulation models (GCMs) or Earth system models of intermediate complexity (EMICs) which simulate an increase in climate sensitivity for colder than present-day climate (e.g., Colman & McAvaney, 2009;Kutzbach et al, 2013;Pfister & Stocker, 2017).…”
Section: Introductionmentioning
confidence: 86%
“…This implies that ECS based on atmosphere-ocean climate models will underestimate warming on millennial timescales. If Earth system feedbacks are treated as additional forcings, as they generally are for example in ECS estimates from the Last Glacial Maximum, then the overall assessed paleoclimate constraints 7,8,446 also support the consensus range of ECS, including its upper bound, but do not constrain it further.…”
Section: Paleoclimatementioning
confidence: 99%